2019
DOI: 10.1002/jac5.1077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of clinical pharmacy services in a pediatric HIV clinic

Abstract: Objectives The objectives of this study were to characterize and analyze clinical pharmacists' interventions in a pediatric human immunodeficiency virus clinic. Methods This retrospective review assesses interventions documented by pediatric pharmacists. The percent of patients with an undetectable viral load at baseline, prior to implementation of pharmacy services, was compared with the viral load at a 7‐year follow‐up visit. Mean log10 viral loads at years 1 and 7 were compared to baseline and the mean chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This statement can be justified by the significant increase of patients with an undetectable viral load based on interventions made by clinical pharmacists. These results can be concurred by another report, which found nearly 1500 clinical interventions made by pharmacists who cared for HIV-positive patients at a Veteran’s Affairs Medical Centre (VAMC) (Morris et al 2019 ). Currently, there are no data available from South Africa that investigate the role of the clinical pharmacist in the utilisation of an ARV-stewardship programme.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This statement can be justified by the significant increase of patients with an undetectable viral load based on interventions made by clinical pharmacists. These results can be concurred by another report, which found nearly 1500 clinical interventions made by pharmacists who cared for HIV-positive patients at a Veteran’s Affairs Medical Centre (VAMC) (Morris et al 2019 ). Currently, there are no data available from South Africa that investigate the role of the clinical pharmacist in the utilisation of an ARV-stewardship programme.…”
Section: Introductionsupporting
confidence: 74%
“…Morris et al ( 2019 ) reported that interventions made by clinical pharmacists, as part of the interdisciplinary care team, contributed towards improved viral loads in paediatric patients. This statement can be justified by the significant increase of patients with an undetectable viral load based on interventions made by clinical pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically looking at clinical endpoints, the percentage of patients with an undetectable viral load increased from 12.1% to 65.8% during the study period ( P = .0094). The mean viral load decreased from baseline (4.37 SD 1.09 copies/mL vs 3.95 SD 1.22 copies/mL P = .0042) (Table ) …”
Section: Clinical Outcomesmentioning
confidence: 96%